Efisiensi E-Court dalam Pelaksanaan Perkara di Pengadilan Agama Gresik - Muhammad Wabi Zadin Ka'af; Nur Faiza; Naily Velayati (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
E-Court is the implementation of PERMA Number 7 of 2022 concerning Electronic Court Administration of Cases and Trials in Courts, implemented by the Gresik Religious Court since 2019 as an effort to provide services to the public seeking justice in the civil sector by registering cases online. This study describes how efficient e-Court at the Gresik Religious Court is in providing case services to the public seeking justice. The research design used in this study is included in the category of qualitative legal research. The results of the study indicate that the implementation of e-Court at the Gresik Religious Court has created effectiveness in providing services. However, there are still challenges in its implementation, such as the adaptation of a small portion of the community. Overall, the benefits are much greater. The conclusion obtained from this study shows that the implementation of e-Court in the Gresik Religious Court has been running quite efficiently, especially in terms of administrative efficiency and services for professional users, as seen from the Number of Cases Registered via e-Court, Increase in the number of cases registered electronically, Reduction in Case Processing Time, Reduction in Queues at PTSP, User Satisfaction Level, Efficiency of Court Operational Costs, Success Rate of Online Payments, Accessibility and Transparency.